EXPERIENCE OF USING COMPLEX REHABILITATION TREATMENT OF PATIENTS WITH CHRONIC INFLAMMATORY DISEASES OF UTERINE APPENDAGES - S. V. Hutieva; L. V. Majsuradze; L. V. Tsallagova (Кубанский научный медицинский вестник, 2017)
Aim. To substantiate the possibility of using modern drug-free technologies in the treatment of chronic inflammatory diseases of uterine appendages.Materials and methods. During the study, 65 patients with chronic inflammatory diseases of uterine appendages were divided into study and control groups. 30 patients of the main group following a traditional medical treatment in the first phase of rehabilitation received a course of quantum therapy. Laser therapy was carried out using the apparatus of RIKTA-02 percutaneous method to the area of the womb. The course of treatment ranged from 5 to 10 procedures. In the second phase of rehabilitation therapy the following treatment course using teraklitau clay was carried out after 3-4 weeks. The control group consisted of 35 patients who underwent the treatment of inflammatory diseases of the uterine appendages according to the standard scheme. Women in both groups underwent clinical, laboratory, immunological, hormonal, and instrumental methods of examination.Results. Stage integrated non-pharmacological treatment of chronic inflammatory processes of uterine appendages had anti-inflammatory, immunocorrective and vasoactive effect.Conclusion. The use of clays of teraklitau and laser therapy in the treatment of inflammation of the uterine appendages has led to persistent therapeutic effect and significantly improved the quality of life in 85% of patients.